Search for Gravitational Waves from a Long-lived Remnant of the Binary Neutron Star Merger GW170817 - Abbott, R.; Araya, M. C.; Atallah, D. V.; Aubin, F.; Bacon, P.; Ballmer, S. W.; Barclay, S. E.; Barker, D.; Barta, D.; Beniwal, D.; Berger, B. K.; Bernuzzi, S.; et al. (The Astrophysical journal, 2019)
One unanswered question about the binary neutron star coalescence GW170817 is the nature of its post-merger remnant. A previous search for post-merger gravitational waves targeted high-frequency signals from a possible neutron star remnant with a maximum signal duration of 500 s. Here, we revisit the neutron star remnant scenario and focus on longer signal durations, up until the end of the second Advanced LIGO-Virgo observing run, which was 8.5 days after the coalescence of GW170817. The main physical scenario for this emission is the power-law spindown of a massive magnetar-like remnant. We use four independent search algorithms with varying degrees of restrictiveness on the signal waveform and different ways of dealing with noise artefacts. In agreement with theoretical estimates, we find no significant signal candidates. Through simulated signals, we quantify that with the current detector sensitivity, nowhere in the studied parameter space are we sensitive to a signal from more than 1 Mpc away, compared to the actual distance of 40 Mpc. However, this study serves as a prototype for post-merger analyses in future observing runs with expected higher sensitivity.